Dissection and function of autoimmunity-associated TNFAIP3 (A20) gene enhancers in humanized mouse models - Upneet K. Sokhi (Nature Portfolio, 2018)
The human TNFAIP3 gene, which encodes for A20, is associated with autoimmune diseases. Here, the authors use BAC transgenics combined with CRISPR- and recombineering-mediated genome editing to dissect in vivo and in primary immune cells, the role of enhancers regulating TNFAIP3.